ANALISIS METODE PENENTUAN HARGA POKOK PESANAN TERHADAP BESARNYA LABA PADA USAHA KERIPIK SINGKONG MORO SENENG DI LAMPUNG TIMUR - Andi Arizal; Tukasno Tukasno (DINAMIKA: Jurnal Manajemen Akuntansi, Bisnis dan Kewirausahaan, 2018)
The purpose of this study is to analyze the calculation of the cost of chips production using the full cost method and variable costs to profit in the "MORO SENENG" cassava chips business. The research method used is to use the full cost and variable costs. The results of the calculation of the cost of production with the full costing method amounted to Rp.212,588 with a selling price of Rp.400, the profit that can be generated in November 2017 is Rp.187,412. So the net profit per month obtained is Rp. 16,435,000. The results of the calculation of production costs using the variable costing method amounted to Rp.180,633 with a selling price of Rp.400, the profit that can be generated in November 2017 amounted to Rp.219,367. So the monthly net profit earned is Rp.23,618,000. Calculation of the cost of production with the full costing method and the variable costing method has differences. In the calculation of the cost of production with the cost of production method produced is greater than the calculation of the cost of production with the variable cost method. The difference in production costs between the two methods is: Rp.32,222 per unit, the total production of cassava chips as much as 120,000 packs so the difference in production costs during November 2017 is Rp.3,834,666.